Scale Matters The Quality of Quantity in Human Culture and Sociality - Widlok, Thomas; Cruz, M. Dores (Edition Kulturwissenschaft, 2022)
Scale matters. When conducting research and writing, scholars upscale and downscale. So do the subjects of their work - we scale, they scale. Although scaling is an integrant part of research, we rarely reflect on scaling as a practice and what happens when we engage with it in scholarly work. The contributors aim to change this: they explore the pitfalls and potentials of scaling in an interdisciplinary dialogue. The volume brings together scholars from diverse fields, working on different geographical areas and time periods, to engage with scale-conscious questions regarding human sociality, culture, and evolution. With contributions by Nurit Bird-David, Robert L. Kelly, Charlotte Damm, Andreas Maier, Brian Codding, Elspeth Ready, Bram Tucker, Graeme Warren and others.